Test analysis of anti-friction/wear of Fullerene C60 lubricating oil to planetary gear shaft - LIU Guoliang; ZHAO Xinhao (Jixie chuandong)
ObjectiveEffective lubrication is one of the most efficient methods for reducing friction and minimizing wear on metal component surfaces in mechanical motion pairs. To address the rapid friction and wear failure of the planetary gear shaft in differential assemblies, this study investigates the anti-wear and friction-reduction effects of fullerene C60 nano-carbon sphere lubricant on planetary gear shafts.MethodsFriction and wear experiment were conducted under the action of fullerene C60 lubricant to analyze the influence of C60 nano-carbon sphere concentration on the friction coefficient and wear scar surface morphology. Additionally, a transmission assembly fatigue life test bench was utilized to perform fatigue wear experiments on the differential planetary gear shaft, observing the friction-reducing effects of C60 nano-carbon spheres on the gear shaft.ResultsThe analysis results demonstrated that the average friction coefficient under the action of fullerene C60 nano-carbon sphere lubricant was as low as 0.080 1, representing a 71.1% reduction compared to the base lubricant. Furthermore, the wear on both ends of the planetary gear shaft pins decreased by approximately 60%.